Frequency of Retinopathy in Newly Diagnosed Patients of Type 2 Diabetes Mellitus - Sohail Zia, Qaim Ali Khan, Kashif Jamil, Yasir Iqbal (Pakistan Journal of Ophthalmology, 2018)
Purpose: To find out the frequency of retinopathy in newly diagnosed patients of type 2 diabetes mellitus. Material and Methods: After the approval of the hospital ethical committee and informed verbal consent of the patients the study was conducted in the out patients department of medicine, DHQ Hospital, Faisalabad. All patients of either sex (Non-probability consecutive sampling) were included, who were diagnosed within two months as type 2 diabetes mellitus. Diagnosis of Diabetes was done by reports of > 200 mg/dl on two consecutive base line random blood sugar (RBS), fasting blood sugar (FBS) and Glycosylated hemoglobin (HBA1c). All the patients underwent dilated retina examination with +90 Diopter lens on biomicroscopic slit lamp and diabetic retinopathy was labeled on the basis of presence of fundus findings. Results: The study was completed in a period of 7 months from Sep 2010 to March 2011. A total of 196 patients fulfilling the criteria were included. Age range was 31 to 60 years with a mean age of 50.95 ± 10.12 years. Diabetic retinopathy was observed in 25 (12.75%) patients with newly diagnosed type 2 diabetes mellitus. The HbA1C (%) was found to be 9.5 ± 1.6 in the patients with diabetic retinopathy and 7.4 ± 2.5 in patients without diabetic retinopathy. Conclusion: We found that the frequency of retinopathy in newly diagnosed patients of type 2 diabetes mellitus is 12.75% and we stress the value of in depth ophthalmic assessment of every patient of diabetes at the time of diagnosis.